Analysis of the Level of Satisfaction of E-Learning Users at PGRI Madiun University Using the Pieces Method. - Nugrahanti, Fatim; Novietasari, Eka Resty; Fatihah, Kahfi Amani (LPPM STIKI Malang, 2024)
The development of technology is a way to quickly disseminate information to users and can help solve problems faced by an institution. The level of user satisfaction with the Universitas PGRI Madiun e-learning system uses the PIECES method (Performance, Information, Economy, Control, Efficiency, and Service). This method was chosen because it is able to identify various aspects of system performance that affect user experience. This study was conducted by collecting data through questionnaires distributed to system users, namely students and lecturers using the Googleform platform. The results of the analysis showed that the Performance and Service aspects obtained the highest satisfaction scores, which indicated that the system was running stably and providing good service to users. However, the Control and Efficiency aspects require improvement, especially regarding ease of access and management of security features. These findings are expected to be input for e-learning system managers to improve the quality of service and overall user experienceThe development of technology is a way to quickly disseminate information to users and can help solve problems faced by an institution. The level of user satisfaction with the Universitas PGRI Madiun e-learning system uses the PIECES method (Performance, Information, Economy, Control, Efficiency, and Service). This method was chosen because it is able to identify various aspects of system performance that affect user experience. This study was conducted by collecting data through questionnaires distributed to system users, namely students and lecturers using the Googleform platform. The results of the analysis showed that the Performance and Service aspects obtained the highest satisfaction scores, which indicated that the system was running stably and providing good service to users. However, the Control and Efficiency aspects require improvement, especially regarding ease of access and management of security features. These findings are expected to be input for e-learning system managers to improve the quality of service and overall user experience. Keywords E-Learning, User Satisfaction, PGRI Madiun University, Pieces Method.